Asymptotic Equivalence of Triangular Differential Equations in Hilbert Spaces - Dang Dinh Chau; Vu Tuan (Український математичний журнал, 2005)
In this article, we study conditions for the asymptotic equivalence of differential equations in Hilbert spaces. We also discuss the relationship between the properties of solutions of differential equations of triangular form and those of truncated differential equations. Вивчено умови асимптотичної еквівалентності диференціальних рівнянь у гільбертових просторах. Розглянуто також зв'язок між властивостями розв'язків диференціальних рівнянь трикутної форми та неповних диференціальних рівнянь.